2013
DOI: 10.3991/ijep.v3is3.2768
|View full text |Cite
|
Sign up to set email alerts
|

Constructivist Multi-Access Lab Approach in Teaching FPGA Systems Design with LabVIEW

Abstract: Abstract-Embedded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Previous research has shown that constructivist learning strategies are effective in promoting student interaction and producing positive outcomes [11][12]. Research has also explored the affective and cognitive domains of learning, including motivation and student conceptions [13].…”
Section: Perception Of Engineering Students On Social Constructivist ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that constructivist learning strategies are effective in promoting student interaction and producing positive outcomes [11][12]. Research has also explored the affective and cognitive domains of learning, including motivation and student conceptions [13].…”
Section: Perception Of Engineering Students On Social Constructivist ...mentioning
confidence: 99%
“…Earlier research has provided evidence supporting the effectiveness of constructivist learning strategies in promoting student interaction and producing positive outcomes [11][12]. In addition, numerous studies have demonstrated that constructivist learning environments have positive effects on "creativity, metacognitive skills, critical thinking, and problem-solving" [57][58][59][60][61][62].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The said graduate program accepts applications from students of various undergraduate programs. The distribution of students accepted to 2013-2014 Electrical-Electronics Engineering Turkish Graduate Program with thesis according to their Undergraduate Program are given in Table II. Literature research shows that text-based programming method is recommended more commonly [16]; only one paper mentions the use of LabVIEW FPGA Module [17]. The reason is the earliest developed method in HDLs being text based.…”
Section: Introductionmentioning
confidence: 99%